Probing the interaction of Rh, Co and bimetallic Rh–Co nanoparticles with the CeO2 support: catalytic materials for alternative energy generation. Issue 40 (29th September 2015) - Varga, E.; Pusztai, P.; Óvári, L.; Oszkó, A.; Erdőhelyi, A.; Papp, C.; Steinrück, H.-P.; Kónya, Z.; Kiss, J.
Abstract : Significant Rh agglomerization occurs and oxygen transfer from ceria to Rh takes place. Co induces the formation of smaller crystallites of ceria. Strong dissolution of Co is experienced. Abstract : The interaction of CeO2 -supported Rh, Co and bimetallic Rh–Co nanoparticles, which are active catalysts in hydrogen production via steam reforming of ethanol, a process related to renewable energy generation, was studied by X-ray diffraction (XRD), high resolution electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS) and low energy ion scattering (LEIS). Furthermore, diffuse reflectance infrared spectroscopy (DRIFTS) of adsorbed CO as a probe molecule was used to characterize the morphology of metal particles. At small loadings (0.1%), Rh is in a much dispersed state on ceria, while at higher contents (1–5%), Rh forms 2–8 nm particles. Between 473–673 K pronounced oxygen transfer from ceria to Rh is observed and at 773 K significant agglomeration of Rh occurs. On reduced ceria, XPS indicates a possible electron transfer from Rh to ceria. The formation of smaller ceria crystallites upon loading with Co was concluded from XRD and HRTEM; for 10% Co, the CeO2 particle size decreased from 27.6 to 10.7 nm. A strong dissolution of Co into ceria and a certain extent of encapsulation by ceria were deduced by XRD, XPS and LEIS. In the bimetallic system, the presence of Rh enhances the reduction of cobalt and ceria. During thermal treatments, reoxidation of Co occurs, and Rh agglomeration as well as oxygen migration from ceria to Rh are hindered in the presence of cobalt.